Impact of Oil Price Shocks on Crypto and Conventional Financial Assets during Financial Crises: Evidence from the Russian Financial Market - Ullah, Mirzat; Sohag, Kazi; Nawaz, Farrukh; Mariev, Oleg; Kayani, Umar; Mayburov, Igor; Doroshenko, Svetlana (International Journal of Energy Economics and Policy, 2024)
This study offers a multidimensional solution to mitigate the risk raised due to oil price volatility for navigating investments within the Russian financial landscape. This study assesses spillover effects between crypto assets and traditional financial assets encompassing equities, bonds, precious metals, foreign currency reserves, and crude oil prices. It adopts a significant temporal perspective to assess the potential ramifications of various financial crises, including global health crises and regional conflicts, on oil prices. Utilizing a daily frequency dataset spanning from January 1, 2018, to December 30, 2023, this study investigates the contagion effects of financial crises across normal, bullish, and bearish market conditions. It introduces oil price shocks for the first time to effectively gauge the impact of exogenous shocks on both crypto and conventional asset classes. Additionally, the study employs Cross Quantilogram (CQ) and TVP-VAR spillover estimation techniques to examine interconnectedness among the underlined assets. Furthermore, the study utilizes the quantile wavelet coherence estimation model to unveil volatility patterns, laying the groundwork for hypotheses related to diversification, hedging, and safe-haven investment strategies among the assets. The findings underscore the effectiveness of crypto assets in diversifying risk and serving as a hedge, particularly evident during crises, leading to heightened volatility. Conversely, government-owned bonds exhibit the lowest resilience to external shocks. Moreover, the dynamic interconnectedness among assets provides guidance to investors for implementing the proposed hypotheses that underscores the importance of prudent asset allocation policies for risk management, optimizing portfolio utilization.